5-step algorithm to accelerate the prediction of [Au 25 (SR) 19 ] z clusters ( z = 1−, 0, 1+) - Tlahuice-Flores, A. (RSC advances, 2024)
Prediction of the structure of thiolated gold clusters is time demanding, and new strategies are needed to expedite this process. In this study, using one five-step algorithm and dispersion corrected density functional theory (DFT-D) calculations, new models are proposed for neutral and charged Au 25 (SR) 19 clusters that contain one extra ligand with respect to the ubiquitous Au 25 (SR) 18 cluster. The algorithm counts for constituting tetrahedra/octahedra units of related isomers, and it provides their energy order. In general, one structure comprising one Au 11 inner core is found as energy minima of neutral and charged Au 25 (SR) 19 clusters. Therefore, our new neutral structure is 0.20 eV (–CH 3 and TPSS) more stable than the previously reported one. With respect to neutral and anionic structures containing inner cores with C 2v symmetry, ultraviolet-visible/circular dichroism profiles are similar.